Swedish Plectida (Nematoda). Part 1. Domorganus suecicus sp. n. from Skagerrak - Holovachov, Oleksandr (Zootaxa, 2012)
A new species of Domorganus, D. suecicus sp. n., is described from bottom sediments collected in Skagerrak off the westcoast of Sweden. It is characterised by its long body (1.3–1.6 mm), lateral field originating immediately posterior toamphid, excretory pore located at the level of basal pharyngeal bulb, absence of advulval sensilla, straight spicules andabsence of gubernaculum. The new species has a unique set of characters (position of excretory pore and absence of thegubernaculum) separating it from all other known species of the genus. It shows some resemblance to the previouslydescribed species D. acutus and D. subtilis in body size and most measurements, but can be easily separated from both bythe relatively longer tail, shorter spicules, position of the anterior end of the lateral field near amphid, position of theexcretory pore anterior to pharyngo-intestinal junction, and absence of gubernaculum. A tabular compendium of species of the genus Domorganus is also given.